Determination of the energy consumption trend of a wine company as a key element for sustainable innovative development - López-Leyva, Josué Aarón; Cortés-Ruíz, Alejandra; Hernandez Serrano, M.F.; Sarmiento-Leyva, Luisa Fernanda; Sanchez Castro, I. (My University, 2020)
The determination of the energy consumption trend of a wine-producing company pilot is presented. The analysis of the energy trend is important because, concerning the Energy Efficiency Indicators and Significant Energy Use, it is possible to propose innovation for processes and organizational structure in the company based on a customized Energy Management System framework. As a result, the trend and its seasonality are determined, which allows determining the relationship between the productivity of the company and energy consumption (e.g. kWh/kg of grapes processed/year). Thus, an energy consumption reduction of up to 17% is proposed, which is equivalent to a Greenhouse Gas Emissions reduction of up to ≈2 ton-CO2/year.
Indexación Scopus
Keywords: Productivity; Energy consuption; Tecnologycal Innovation; Companies; Yools; Market research; Campus Ensenada